1997
DOI: 10.1046/j.1365-3156.1997.d01-269.x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni‐related morbidity on Ukerewe Island, Tanzania: clinical, ultrasonographical and biochemical parameters

Abstract: SummaryOne thousand six hundred and ninety-five inhabitants of 3 rural villages on Ukerewe Island, Lake Victoria, Tanzania, were examined by clinical, parasitological, ultrasonographic and-in part-serological means to evaluate Schistosoma (S.) mansoni-related morbidity on a community level. Villagers frequently complained of typical colitis symptoms (abdominal pain 80.1%, bloody stools 43.1%, diarrhoea 35.1%); haematemesis, on the other hand, was rare (and reports doubtful in most cases). 16.9% of the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
64
4
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 31 publications
15
64
4
2
Order By: Relevance
“…Decreases in the thickness of portal vein walls and in echogenic bands have been detected after praziquantel therapy (HOMEIDA et al, 1988;DOEHRING-SCHWERDTFEGER et al, 1989: OH-MAE et al, 1992WIEST et al, 1993;CAI>~ al., i997;GERSPACHER-LARA et aI, 1997;BOISIER et al, 1998). Assay of serum levels of fibrosis markers may be a useful supplementary tool for monitoring changes in liver fibrosis (SHAHIN et aZ., 1992;KARDORFF et al, 1997;OBERTI et al, 1997;ESTERRE et al, 1998;RICARD-BLUM et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in the thickness of portal vein walls and in echogenic bands have been detected after praziquantel therapy (HOMEIDA et al, 1988;DOEHRING-SCHWERDTFEGER et al, 1989: OH-MAE et al, 1992WIEST et al, 1993;CAI>~ al., i997;GERSPACHER-LARA et aI, 1997;BOISIER et al, 1998). Assay of serum levels of fibrosis markers may be a useful supplementary tool for monitoring changes in liver fibrosis (SHAHIN et aZ., 1992;KARDORFF et al, 1997;OBERTI et al, 1997;ESTERRE et al, 1998;RICARD-BLUM et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These morbidities have shown a strong relationship. [19] In this study we determined if minimally trained practitioners can use ultrasound to identify acute pathology of chronic infections in rural Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Use of portable ultrasound improves accessibility and removes some of the constraints of upkeep. Studies [15][16][17][18][19][20] have shown that the introduction of ultrasound can significantly alter treatment plan. In 43% of cases in Rwanda, ultrasound changed the initial management plan, involving surgical procedure, medication, clinic referral and others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations